Modification of Technology Acceptance Model in Regional Development Information System - Elsya Herwiyanti; Wahyu Agus Winarno; Muhammad Miqdad (Jurnal Akuntansi dan Pajak, 2023)
The aim of this study is to analyze the factors that influence the acceptance of the Regional Development Information System (SIPD) using the Technology Acceptance Model (TAM) theory. Based on the TAM theory, there are two perceptions that influence behavioral intentions in accepting the use of the system, namely perceived of usefulness and perceived ease of use. Design of this research is modified among Technology Acceptance Model 3, Perceived Risk, and Trust as the predictors. The subject of the study are the users of SIPD who are employees of each department in Banyuwangi . The results of this study are expected to indicate the factors that can affect the optimization of SIPD acceptance.